Situation-based Learning Model Implementation through Thematic Learning as an Effort to Improve the Primary School Students' CPS Ability - Ramdan, Muhamad; Hanifah, Nurdinah; Isrokatun, Isrokatun (Mimbar Sekolah Dasar, 2019)
This research aims at measuring the improvement of the students’ CPS ability through the SBL model implementation through thematic learning. This research employed a quasi-experimental design with non-equivalent control group design involving all fourth grade students in public primary schools in Sumedang Regency. Meanwhile, the sample used in the research was one of public primary schools in North of Sumedang Regency by determining that 30 students of class IV-A included in the experimental class, and 32 students of class IV-B included in the control class. Based on the test instrument of CPS ability, the research results revealed that the SBL model implementation was able to improve significantly the CPS ability in thematic learning in the experimental class.